Three-dimensional-printed headcap with embedded microdrive system for customizable multi-region brain recordings with neural probes - Hartner, Jeremiah P.; Yi, Dongyang; Zhu, Harrison L.; Watson, Brendon O.; Chen, Lei (Frontiers in Neuroscience, 2024)
Electrophysiological recordings from single neurons are crucial for understanding the complex functioning of the brain and for developing eventual therapeutic interventions. For electrophysiology, the accuracy and fidelity of invasive implantations of small devices remains unmatched. This study introduces an innovative, cost-efficient, 3D-printed headcap with embedded microdrive (THEM) system designed to streamline the manual labor-intensive in-vivo electrode implantation process for efficient and precise multi-region brain neural probe implantations. A custom bregma-referenced headcap design and fabrication, embedded microdrive integration, and upper support structure for probe packaging are described. With the Sprague Dawley rat as test species and medial prefrontal cortex and CA1 of the dorsal hippocampus as targets, surgeries and electrophysiological recordings were conducted to test the capability of the THEM system as compared to conventional surgical methods. By shifting manual stereotaxic alignment work to pre-surgical preparation of a fully assembled headcap system, incorporating fully preassembled upper support framework for packaging management, and easy customization for specific experiment designs and probe types, our system significantly reduces the surgical time, simplifies multi-implant procedures, and enhances procedural accuracy and repeatability. The THEM system demonstrates a significant improvement over conventional surgical implantation methods and offers a promising tool for future neuroscience research.